Enhanced Photocurrent Response of Graphene Nanosheets-SnO2 Nanocomposites via a Facile Hydrolysis Method. (10th November 2015) - Wang, Yu-Fen; Wang, Xin; Li, Xi-Fei; Li, De-Jun; Sun, Yuan-Wei; Zhang, Xian-Xi
Graphical Abstract: Highlights: A facile and efficient hydrolysis process was proposed to create graphene nanosheets-SnO2 nanocomposites. SnO2 nanoparticle (∼10 nm in size) uniformly dispersed on graphene sheets. The photocurrent of GSCS was 130 μA/cm 2, which is about 4 times higher than that of SnO2 . ABSTRACT: A facile and efficient hydrolysis process was proposed to create graphene nanosheets-SnO2 nanocomposites (GSCS). The hydrolysis reaction results in the formation of pure phase SnO2 nanoparticle (∼10 nm in size) uniformly dispersed on graphene sheets while simultaneously cause reduction of graphene oxide. The as-prepared materials were characterized in detail by X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), Raman spectra and X-ray photoelectron spectroscopy (XPS). In the investigation of photocurrent response properties, it was found that the photocurrent of GSCS was 130 μA/cm 2, which is about 4 times higher than that of SnO2 .